Overcoming challenges in advanced melanoma treatment: The value of real-world data - van Not, Olivier (Utrecht University, 2024)
Each year, approximately 800 to 900 patients in the Netherlands are diagnosed with metastatic (i.e. unresectable) melanoma. Several new systemic therapies have become available for the treatment of unresectable melanoma. These therapies, including targeted therapy and immune checkpoint inhibitors, have significantly improved survival. However, several challenges remain in the treatment of this disease. Using data from the Dutch Melanoma Treatment Registry, this dissertation addresses some of these challenges. It describes research on changes in the treatment landscape of unresectable melanoma, on the optimization of the treatment of unresectable melanoma, and on specific subgroups of patients. COVID-19 has had a significant impact on melanoma care in the Netherlands. Nevertheless, the survival of patients with unresectable melanoma has improved over the years. We also observed that a portion of patients experience long-term survival after treatment with immune checkpoint inhibitors. Furthermore, we found that retreatment of patients with targeted therapy, after previous treatment with targeted therapy, results in a response in 43% of patients. Additionally, we investigated how the treatment of severe adverse events caused by immune checkpoint inhibitors affects survival. Lastly, this dissertation describes the results of the treatment of patients with both unresectable melanoma and a hematological malignancy, the treatment with immune checkpoint inhibitors of patients with melanoma brain metastases, the treatment of patients with acral melanoma, and the influence of having a BRAF or NRAS mutation on the response to immune checkpoint inhibitors.
Keywords: advanced melanoma; immune checkpoint inhibitors; targeted therapy; survival